Daytime HONO formation in the suburban area of the megacity Beijing, China - Yang, Q.; H. Su; X. Li; Cheng, Y. F.; Lu, K. D.; Cheng, P.; Gu, J. W.; Guo, S.; Hu, M.; L.M. Zeng; T. Zhu; Zhang, Y. H. (Science China-ChemistryScience China-Chemistry, 2014)
Nitrous acid (HONO), as a primary precursor of OH radicals, has been considered one of the most important nitrogen-containing species in the atmosphere. Up to 30% of primary OH radical production is attributed to the photolysis of HONO. However, the major HONO formation mechanisms are still under discussion. During the Campaigns of Air Quality Research in Beijing and Surrounding Region (CAREBeijing2006) campaign, comprehensive measurements were carried out in the megacity Beijing, where the chemical budget of HONO was fully constrained. The average diurnal HONO concentration varied from 0.33 to 1.2 ppbv. The net OH production rate from HONO, P (OH)(HONO)(net), was on average (from 05:00 to 19:00 h) 7.1 x 10(6) molecule/(cm(3) s), 2.7 times higher than from O-3 photolysis. This production rate demonstrates the important role of HONO in the atmospheric chemistry of megacity Beijing. An unknown HONO source (P (unknown)) with an average of 7.3 x 10(6) molecule/(cm(3) s) was derived from the budget analysis during daytime. P (unknown) provided four times more HONO than the reaction of NO with OH did. The diurnal variation of P (unknown) showed an apparent photo-enhanced feature with a maximum around 12:00 h, which was consistent with previous studies at forest and rural sites. Laboratory studies proposed new mechanisms to recruit NO2 and J(NO2) in order to explain a photo-enhancement of of P (unknown). In this study, these mechanisms were validated against the observation-constraint P (unknown). The reaction of exited NO2 accounted for only 6% of P (unknown), and P (unknown) poorly correlated with [NO2] (R = 0.26) and J(NO2)[NO2] (R = 0.35). These results challenged the role of NO2 as a major precursor of the missing HONO source.
Keywords: atmospheric boundary-layer; budget; chemistry; differential optical-absorption; heterogeneous; heterogeneous hydrolysis; hono; nitrous acid; nitrous-acid hono; oh; photochemical production; rural site; simulated vertical profiles; unknown source; urban areas